Transfer Matrix Method to Vibration Analysis of Rotors with Coupler Offsets - Chao-Yang Tsai; Shyh-Chin Huang (Shock and Vibration)
In this paper a general transfer matrix method (TMM) for rotors containing global and local coupler offset was derived. Rotor response due to imbalances and offsets are then studied via the developed method. The studies showed both global and local offsets played as an external excitation that is a combined effect of all the elements behind the offset. Differences between global offset and local offset were compared and the results showed both types basically retain the same mode patterns but different jumps at the offset. The global offset, yet, imposed more significant dynamic effects since all the offsets accumulate thereafter. The whirling orbits in front and behind the offset were illustrated as well. The results, as expected, showed global offset appeared much larger radii especially after offset. The rotor's whirling orientation reversed, as rotation fell within a certain range and this feature was not changed by offsets. The TMM proposed by this study can be well applied to multiple global and local offsets.